Optimalisasi Pemberdayaan Masyarakat Berbasis Ekonomi Kreatif Sebagai Upaya Realisasi Desa Wisata Berkearifan Lokal: (Studi Kasus: Sentra Industri Sarung Goyor Desa Wanarejan Utara Kabupaten Pemalang) - Mufidatul Nur Laeli; Wilda Yulia Rusyida (JIEF : Journal of Islamic Economics and Finance, 2021)
This research is intended to find an accurate of data whether the existence of the Goyor sarong center as a creative economy can create a tourism village with local wisdom for the preservation of Indonesian local culture. This research was conducted at the Goyor Sarong Industrial Center, North Wanarejan Village, Pemalang Regency using qualitative research methods with data collection techniques using interviews, observations and questionnaires. The results showed that the Sarong Goyor Industrial Center can be used as a tourist village with local wisdom. One of the potentials is to have a unique and distinctive tourist attraction from the socio-cultural community, supported by being exported to the international market. However, there are still obstacles faced, namely the inadequate quality of human resources and also supporting infrastructure in terms of production and marketing. With this, it is very necessary to have an active role from various parties, both the local community and the government.